2011
DOI: 10.1130/l159.1
|View full text |Cite
|
Sign up to set email alerts
|

Late Miocene–Pliocene range growth in the interior of the northeastern Tibetan Plateau

Abstract: The time-space patterns of deformation throughout the Indo-Asian collision zone can place constraints on the processes responsible for the development of high topography. Although most agree that high topography associated with the Tibetan Plateau expanded throughout the Cenozoic, it is increasingly being recognized that portions of the present-day plateau experienced a protracted history of deformation starting before or shortly after collision. Deciphering the history of deformation in these regions is centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(96 citation statements)
references
References 89 publications
(176 reference statements)
3
92
0
1
Order By: Relevance
“…1). Although some ranges in northeastern Tibet likely experienced deformation in Eocene time Clark et al, 2010;Duvall et al, 2011;Yuan et al, 2013), widespread exposures of Neogene-Quaternary basin fi ll suggest that most of these ranges are associated with thrust faults that initiated during the middle to late Miocene (Fang et al, 2005;Zheng et al, 2006;Lease et al, 2007Lease et al, , 2012aLease et al, , 2012bCraddock et al, 2011a;Hough et al, 2011;Zhang et al, 2012;Duvall et al, 2013;Yuan et al, 2013, and references therein). Few of these fault networks have experienced instrumental earthquakes (Global Centroid Moment Tensor Catalog, 2012); however, geomorphic observations along fault-bounded range fronts indicate that many have been active during the Holocene (Peltzer et al, 1988;Meyer et al, 1998;Van der Woerd et al, 2001;Hetzel et al, 2004;Champagnac et al, 2010;Hetzel, 2013;Zheng et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…1). Although some ranges in northeastern Tibet likely experienced deformation in Eocene time Clark et al, 2010;Duvall et al, 2011;Yuan et al, 2013), widespread exposures of Neogene-Quaternary basin fi ll suggest that most of these ranges are associated with thrust faults that initiated during the middle to late Miocene (Fang et al, 2005;Zheng et al, 2006;Lease et al, 2007Lease et al, , 2012aLease et al, , 2012bCraddock et al, 2011a;Hough et al, 2011;Zhang et al, 2012;Duvall et al, 2013;Yuan et al, 2013, and references therein). Few of these fault networks have experienced instrumental earthquakes (Global Centroid Moment Tensor Catalog, 2012); however, geomorphic observations along fault-bounded range fronts indicate that many have been active during the Holocene (Peltzer et al, 1988;Meyer et al, 1998;Van der Woerd et al, 2001;Hetzel et al, 2004;Champagnac et al, 2010;Hetzel, 2013;Zheng et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…The 17-8 Ma event is well reported from many regions of the Qinghai-Tibetan Plateau, particularly from the eastern Kunlun Shan (ca. 20-8 Ma) Duvall et al, 2013); Liupan Shan, Laji Shan and Jishi Shan (13-7 Ma) (Zheng et al, 2006;Lu et al, 2012;Lease et al, 2007Lease et al, , 2011Lease et al, , 2012a; Gonghenan Shan (10-7 Ma) (Craddock et al, 2011); Ela Shan (12-6 Ma) ; Qilian Shan (ca. 20-9 Ma) (George et al, 2001;Zheng et al, 2010;Wang et al, 2011a,b); and Longmen Shan (15-10 Ma) (Deng et al, 2013;Wang et al, 2012) (Fig.…”
Section: Exhumation Timing Of the Laji Shan And Daban Shanmentioning
confidence: 99%
“…However, (1) the timings of basin development are different, as the Xining Basin formed at ca. 52-50 Ma (Dai et al, 2006) and the Qaidam Basin formed during 65-50 Ma (Yin et al, 2008b); (2) the basin mechanisms are different: the Xining Basin developed due to the extension and pulling-apart caused by the clockwise rotation of the Central Qilian Block related to the South Qilian Block, and many growth normal faults have recently been found (Dupont-Nivet et al, 2004, and our unpublished data) dating to the Early Cenozoic; and the basin became a compressive one since the Miocene because of the basinward thrusting of the Laji Shan and the Daban Shan, but the Qaidam Basin developed due to thrusting that had been occurring since the beginning of the basin (Yin et al, 2008a(Yin et al, , 2008b; (3) some recent studies have shown that the region between the present Xining Basin and Qaidam Basin (i.e., Ela Shan, Guide Basin and Xunhua Basin) underwent prolonged uplift during the Paleogene; the Ela Shan was once a structural highland shedding clasts into the Qaidam Basin to the west and the Xining Basin to the east, and no sediments of that period are distributed there (Craddock et al, 2011;Lu et al, 2012); in addition, the Chaka and Gonghe Basins located between the Xining Basin and Qaidam Basin developed only since ca. 11-10 Ma (Craddock et al, 2011;Zhang et al, 2012); (4) the sedimentary environments are different: the Qaidam Basin was dominated by fluvial environments during the Paleogene and by a lacustrine environment during the Neogene (Yin et al, 2008b); however, the Xining Basin was in a lacustrine environment during the Paleogene and in a fluvial one during the Neogene (Zhang et al, 2010a,b;our unpublished data).…”
Section: Mechanisms Of the Two-stage Exhumation Of Laji Shan And Dabamentioning
confidence: 99%
“…In general, uplift of the basin margins during the Cenozoic produced a regional intermontane synclinorium that accumulated mainly fl uvial and lacustrine sediment (Zhou et al, 2006;Yin et al, 2008;Craddock et al, 2011;Zhuang et al, 2011b). A regional unconformity below Paleocene-Eocene strata implies that Cenozoic deposition initiated at 65-49 Ma due to uplift along the northern side of the basin (Yin et al, 2008;Zhuang et al, 2011b).…”
Section: Geologic Settingmentioning
confidence: 99%
“…Both tectonic uplift and climate change can infl uence sedimentation patterns, and thus any causal interpretation of stratigraphy must account for both tectonic and climatic infl uences. Strata preserved within the Qaidam and other nearby basins in the northeastern Tibetan Plateau record tectonic and climatic changes since at least Paleocene time (Pares et al, 2003;Fang et al, 2003Fang et al, , 2007Horton et al, 2004;Zhou et al, 2006;Yin et al, 2008;Craddock et al, 2011;Zhuang et al, 2011b;H.-P. Zhang et al, 2012). Differentiating the tectonic versus climatic controls on sedimentation at any of these localities, however, is complicated by the competing infl uences of both tectonics and climate on sedimentation.…”
Section: Introductionmentioning
confidence: 99%